Passive Techniques for Controlling the Flow in Supersonic Wing - Body Junctions - Blank, S. C. (Cranfield University, 1994)
Junction flows are common to all flight speeds and they are associated with undesirable features such as increases in drag, limitations on performance and at supersonic speeds high heat transfer rates. Junction flows are associated with performance losses in turbomachinery (around 30% of the total pressure losses in an axial turbine) and they can lead to premature detection of military underwater vessels. Junction fairings are widely used at subsonic speeds and correct fairing of the C-141 wing alone, could have resulted in potential fuel savings of approximately US $ 40,000 per year per aircraft which can be roughly translated into a $ 600,000 saving during the lifetime of each airframe. Typically, for a modern transport type of aircraft the wing juncture accounts for between 1 and 2 % of cruise drag and therefore, careful design of the wing junction is necessary. At supersonic speeds, by far the most disadvantageous feature associated with juncture design is high heat transfer rates due to shock / shock interaction. These heat transfer rates are sufficient to cause severe structural damage leading to component burn-off. Typical leading edge temperatures during re-entry for an aerospaceplane, like HOTOL, are around 2000 K, exclusive of increases in temperature caused by the interaction. Although drag reduction may not be so relatively critical at these flight speeds, the potential loss of control components, like stabilising fins, needs to be carefully examined and some configuration re-design may be necessary as a consequence. This research project is aimed at developing a technique through which the disadvantageous features associated with supersonic junction designs can be alleviated. It was found that through re-design of the wing / body junction the maximum mean static pressure local to the fin leading edge could be halved, the strength of the junction vortices could be lowered and the amount of separated flow reduced. The applications of the technology span all vehicles operating within the supersonic flight regime and therefore, the markets to which the technology is applicable are military aircraft, defence systems, aerospaceplanes and commercial supersonic transports. As the technology is, in principle, applicable to the design of commercial supersonic transport aircraft (HSCT) and the market for these vehicles is forecast to be worth up to $ 200 billion (FY 1987) an examination of the issues behind marketing this type of vehicle is presented in the non¬technical section. The presently available data produced by the major manufacturers were found to be lacking in the following areas (a) evaluations of market elasticity, (b) distribution techniques, (c) the availability of acquisition finance and financing techniques, (d) political sensitivity analysis (d) product life cycle analysis and (f) the relationship marketing of the venture.